Ethnographic experiments with artists, designers and boundary objects : exhibitions as a research method - Martinez, Francisco (UCL Press, 2021)
Ethnographic Experiments with Artists, Designers and Boundary Objects is a lively investigation into ethnographic practice. Richly illustrated, it invites the reader to reflect on the skills of collaboration and experimentation in fieldwork and in gallery curation, thereby expanding our modes of knowledge production. Francisco Martínez increases our understanding of the relationship between contemporary art, design and anthropology, imagining creative ways to engage with the contemporary world and developing research infrastructures across disciplines. He opens up a vast field of methodological explorations, providing a language to reconsider ethnography and objecthood while producing knowledge with people of different backgrounds. At the heart of this study are the possibilities for transdisciplinary collaborations, the opportunity to use exhibitions as research devices, and the role of experimentation in the exhibition process. It is critical reading for researchers of Anthropology, Material Culture and Museum Studies, and for any reader with an interest in ethnographic methods.